Analyze The Tax Reduction Policy Implemented by The Government of Timor Leste - Marito Magno; João Belo; Denilson Valdini F. S. Das Neves; Febrinha M. E. Santo; Inácio de Castro Ferreira; Joanico dos Santos Guterres (Jurnal Syntax Transformation, 2025)
This article analyzes the political and economic implications of the VIII Government of Timor-Leste's decision to reduce the selective tax rate. The objective of this research is to assess the impacts of this policy on national economic growth, income distribution, and social welfare. Employing a qualitative approach, the research utilizes government documents, political speeches, and tax data to examine the motivations behind the policy and its effects. The findings suggest that while the reduction in the selective tax aims to stimulate consumption and economic activities, concerns persist regarding long-term fiscal sustainability and the fairness of benefit distribution. A comparative analysis with tax policies in other developing nations highlights potential risks, such as increased reliance on selective taxes and their effects on inflation. Furthermore, the research emphasizes the need for alternative strategies to ensure economic stability and equitable growth. This research contributes to the broader discussion on fiscal policies in Timor-Leste, advocating for a balanced taxation approach that considers both revenue generation and economic equity. The insights gained from this analysis are crucial for policymakers to design effective fiscal strategies that promote sustainable development and enhance social welfare in the country.